2019
DOI: 10.1007/s10875-019-00600-z
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical Stem Cell Transplantation with Post-Transplant Cyclophosphamide for Primary Immune Deficiency Disorders in Children: Challenges and Outcome from a Tertiary Care Center in South India

Abstract: Haploidentical stem cell transplantation (haplo SCT) has emerged as an acceptable alternative to matched family donor transplantation for children diagnosed to have primary immune deficiency disorders (PIDs). We present data over 4 years on the challenges and efficacy of unmanipulated T cell replete haplo SCTs with post-transplant cyclophosphamide (PTCy) in children diagnosed to have PIDs. We performed a retrospective study in the pediatric blood and marrow transplantation unit where all children less than 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 16 publications
0
35
1
Order By: Relevance
“…Recent reports focusing on haploidentical HSCT with PT-Cy in pediatric patients with nonmalignant diseases offer different promising approaches using a variety of conditioning regimens [6][7][8][9][10]. Klein et al reported HSCT of 11 children with nonmalignant disorders showing very good outcomes with limited GvHD, excellent engraftment outcomes and no treatment related mortality using a RIC regimen with fludarabine, melphalan and upfront serotherapy with alemtuzumab [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports focusing on haploidentical HSCT with PT-Cy in pediatric patients with nonmalignant diseases offer different promising approaches using a variety of conditioning regimens [6][7][8][9][10]. Klein et al reported HSCT of 11 children with nonmalignant disorders showing very good outcomes with limited GvHD, excellent engraftment outcomes and no treatment related mortality using a RIC regimen with fludarabine, melphalan and upfront serotherapy with alemtuzumab [9].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient did not survive and died 20 days post HSCT from VOD and CMV pneumonitis. However, there are some recent reports with promising results of successful haploidentical transplants with PT-Cy for patients with HLH [8,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of infection at time of HSCT is associated with poorer outcomes and impacts negatively on survival . Infants older than 3 months whose infection had resolved had similar survival to older infants who were never infected or young infants with/without infection, with survival rates of 82, 90 and 94%, respectively, independent of type of transplant .…”
Section: Discussionmentioning
confidence: 99%
“…HLA-haploidentical transplant for IEI has become an acceptable alternative for patients without matched donors. 11 Historically, haploidentical transplants were associated with high rates of GvHD, graft failure and transplant-related morbidity and mortality. Survival using HLA-HDs was only 66%, significantly inferior to MSD transplants for patients with SCID.…”
Section: Discussionmentioning
confidence: 99%